Investigation of Bacteriocin and Probiotic Properties of Lactic Acid Bacteria from Pastrami - Disli, HB; Gonulalan, Z (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to determine the microbiological quality, LAB profile, phylogenetics of Lactobacillaceae and bacteriocin synthesis potential of pastrami isolates produced in Turkey, Kayseri. The probiotic properties of bacteriocinogen strains were investigated in the second stage of the research. To identify the isolates, MALDI-TOF MS and 16S rRNA sequence analysis methods were used. The bacteriocinogenic properties of the strains were evaluated both phenotypically, using the well diffusion method, and at the gene level, using conventional and RT-PCR. To control the stability of cell-free supernatants of bacteriocinogen strains, tolerance tests for enzyme, temperature and pH were performed. To evaluate the probiotic properties of the strains, we investigated their tolerance to gastric juice and bile salts, susceptibility to antibiotics, and ability to synthesize EPSs. The identification process revealed that the dominant species in pastrami was Latilactobacillus sakei. Based on the analyses performed, it was determined that 15 strains (14.56%) exhibited phenotypic antimicrobial activity against at least one of the selected indicator bacteria. Five strains were found to be positive for at least one of the sakacin P and sakacin Q synthesis genes on molecular analysis, which were confirmed by sequence analysis. Cell-free supernatants of bacteriocinogen strains were found to be tolerant of low pH and different temperature conditions. In conclusion, it has been determined that the Latilactobacillus sakei 2 and Latilactobacillus curvatus 48 strains have significant potential in terms of probiotic and starter culture properties.